About Some Problems of Interdepartmental Interaction when Appointing Socio-Security Payments - M. G. Sedelnikova; A. A. Puzyreva (Сибирское юридическое обозрение, 2019)
Violations of the current legislation on social payments, which have become widespread in recent years, lead to significant budget losses. In part, this is facilitated by the lack of operational interdepartmental interaction of the subject-law enforcement officer with other state bodies that have significant information. Its presence at the law enforcement officer would allow to prevent illegal payments, to prevent plunder of budgetary funds. The Authors propose methods of preventive orientation, in particular, the establishment of additional conditions for obtaining maternal (family) capital, the systematization of legislation on social payments, the acceleration of the creation of a Unified state information system of social security with filling it with new features and functions.